Pergeseran Bahasa Daerah Pada Anak-Anak di Kuala Tanjung Sumatra Utara - NFN Sahril (Ranah: Jurnal Kajian Bahasa, 2018)
This research aims to describe the condition of regional language shift among children in Kuala Tanjung. Afterwards, it will be studied whether the attitude factor and the parents’ role affect the use of regional language. To answer this issue, the researcher involved the societies of Kuala Tanjung who live in the districts of Sei Suka, Medang Deras and Air Putih in Batu Bara Regency, North Sumatra Province. From these populations, samples are taken as many as 20 children from each district. The total sample is 60 people aged 6-12 years (primary education age), 60 parents (30—50 years, married), so the total sample is 120 people. This research used quantitative-qualitative descriptive method. Data collection techniques are observation, questionnaires and interviews through note taking and recording as the research instruments. The result of the research shows the condition of language shift among children in Kuala Tanjung based on percentage analysis of questionnaire data. The use of language in the realm of family and official and unofficial domains in schools shows the dominance of Indonesian language usage. Based on the percentage calculations, almost all respondents' answers indicate a lack of regional language usage by children, although in terms of attitudes, the respondents’ attitude towards regional language usage is quite encouraging, shown by the percentage of questionnaires. However, it does not affect the regional languages defense so that it is concluded that there has been a shift in language. AbstrakPenelitian ini bertujuan untuk menggambarkan kondisi pergeseran bahasa daerah di kalangan anak-anak di wilayah Kuala Tanjung. Lebih lanjut, akan dilihat apakah faktor sikap dan peran orang tua memengaruhi penggunaan bahasa daerah. Untuk menjawab permasalahan tersebut, peneliti menggunakan populasi masyarakat Kuala Tanjung yang berdomisili di Kecamatan Sei Suka, Kecamatan Medang Deras, dan Kecamatan Air Putih, Kabupaten Batu Bara, Provinsi Sumatra Utara. Dari sejumlah populasi tersebut, diambil sampel sebanyak 20 anak-anak dan 20 orang tua dari tiap-tiap kecamatan. Jumlah sampel adalah 60 orang usia 6—12 tahun (usia pendidikan dasar) dan 60 orang tua (30—50 tahun, menikah), total sampel adalah 120 orang. Penelitian ini menggunakan metode deskriptif kuantitatif-kualitatif. Teknik pengumpulan data yang digunakan adalah observasi, kuesioner, dan wawancara yang dilengkapi dengan instrumen penelitian, yaitu pencatatan dan perekaman. Hasil penelitian menunjukkan adanya kondisi pergeseran bahasa di kalangan anak-anak di Kuala Tanjung berdasarkan analisis persentase data kuesioner. Penggunaan bahasa pada ranah keluarga dan ranah resmi dan tidak resmi di sekolah menunjukkan dominannya penggunaan bahasa Indonesia. Berdasarkan perhitungan persentase, hampir semua jawaban responden menunjukkan kurangnya penggunaan bahasa daerah oleh anak-anak walaupun dari segi sikap responden terhadap penggunaan bahasa daerah cukup mengembirakan, yang ditunjukkan oleh hasil persentase kuesioner. Akan tetapi, tidak memberi pengaruh pada pemertahanan bahasa daerah sehingga disimpulkan telah terjadi pergeseran bahasa.